Lower price increases, the bounded rationality of bidders, and underbidding concerns in online agricultural land auctions: The Ukrainian case - Olena Myrna (Journal of Agricultural Economics, 2022)
Auction theory suggests that bidders follow a dominant strategy that is to submit the highest bid equal to the bidder's true valuation in an ascending price auction with independent and private values. Bidders in real-world auctions may deviate from this strategy, resulting in either underbidding—submitting bids lower than the valuation—or overbidding—bidding an amount in excess of the real value. This study utilises data collected from online agricultural land lease auctions in Ukraine that took place between October 2018 and September 2019 to analyse the occurrence of minimal price increases, which may indicate underbidding. It investigates if factors—auction and property characteristics—that typically explain deviations from the dominant strategy—can also explain bidding behaviours in land lease auctions. The estimation using a heteroscedastic probit model reveals that underbidding could reasonably be attributed to low competition, insufficient time to place a subsequent bid, very small bid increments, and cumbersome entry fees.
Keywords: 630; agricultural rental prices; bidding behaviour; online land lease auction; underbidding